The harassed on Facebook a social networking site as the new public sphere - Geronimo, Mary Josephine Andrea Aguilar 1997-; Enriquez, Elizabeth L.; University of the Philippines. College of Mass Communication (2018)
"This research seeks to critically analyze if Facebook serves as a public sphere for discourse and movements against sexual harassment in the Philippines. In a 2016 Social Weather Stations Survey, three in five women in Quezon City alone have experienced sexual harassment. Other have taken it to Facebook to share their experiences which also spark discussion from fellow users. Thus, the paper aims to find out how Facebook members in the country discuss sexual harassment and how the discourse inspires action from the government. The study used the ideas by Jurgen Habermas about the Public Sphere as points of reference and then employs the criticisms on his concepts particularly those drafted by Nancy Fraser. The ideas of the latter are the main bases of the paper in analyzing the potential of Facebook as a Public Sphere. The research concludes that there are several public spheres inside Facebook that circulate counterdiscourses about sexual harassment among participants. This is attained by identifying the deliberations of Facebook users on different sexual harassment-related posts as well as critically looking at how some government offices utilize the platform to disseminate their advocacies and their actions against the issues."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Facebook (Online social network).; Online social networks; Sexual harassment